2019
DOI: 10.3390/ijms20102571
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyproline-Rich Glycoproteins as Markers of Temperature Stress in the Leaves of Brachypodium distachyon

Abstract: Plants frequently encounter diverse abiotic stresses, one of which is environmental thermal stress. To cope with these stresses, plants have developed a range of mechanisms, including altering the cell wall architecture, which is facilitated by the arabinogalactan proteins (AGP) and extensins (EXT). In order to characterise the localisation of the epitopes of the AGP and EXT, which are induced by the stress connected with a low (4 °C) or a high (40 °C) temperature, in the leaves of Brachypodium distachyon, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 84 publications
(101 reference statements)
1
19
0
Order By: Relevance
“…In a previous work, we investigated the response of the hydroxyproline-rich glycoproteins (HRGPs) to temperature stress in leaves. We showed a differential response of the HRGPs to temperature stress with more pronounced changes in the levels of the mRNAs encoding the AGPs at a high temperature [27]. Although the roots and reproductive organs are more sensitive to temperature, the response of the leaves directly affects plant productivity [9,28].…”
Section: Introductionmentioning
confidence: 85%
“…In a previous work, we investigated the response of the hydroxyproline-rich glycoproteins (HRGPs) to temperature stress in leaves. We showed a differential response of the HRGPs to temperature stress with more pronounced changes in the levels of the mRNAs encoding the AGPs at a high temperature [27]. Although the roots and reproductive organs are more sensitive to temperature, the response of the leaves directly affects plant productivity [9,28].…”
Section: Introductionmentioning
confidence: 85%
“…To demonstrate that our protocol has general applicability, we also targeted two genes responsible for cell wall maintenance, encoding fasciclin-like arabinogalactan protein (FLA) and pectin methylesterase (PME) and 2 protein kinase genes from the CDKG group. We have previously found that expression of the FLA gene is upregulated in B. distachyon leaves in response to the temperature stress (Pinski et al, 2019). The inactivation of the second gene, PME, in A. thaliana led to increased susceptibility to salt stress (Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of AGPs in the abiotic stress responses and plant development [ 22 , 23 ], little is known about their function during plant germination under the stressful conditions in which a disturbance of the cell cycle is an additional limiting factor. In B. distachyon (Brachypodium), AGPs have been shown to be involved in temperature stress [ 24 ], but they have yet to be investigated in the context of the response to salt stress.…”
Section: Introductionmentioning
confidence: 99%